LENGTH-WEIGHT STUDIES OF EPINEPHELUS CHLOROSTIGMA E. EOLATUS FROM GULF - Alkahem, Hmoud Fares; Ahmad, Zubair; Al-Dhahi, Amir Ahmad Abdur-Rahman (Journal of Indian Fisheries Association, 2015)
Regression coefficient value (b) of the length-weight relation of Epinepheluschlorostigma was registered as 2.6383, which is significantly (p